“Implementación de un banco de capacitores para corregir el factor de potencia para cargas no lineales en el laboratorio de electromecánica de la Universidad Técnica de Cotopaxi Extensión La Maná bloque b”. - Bohórquez Travez, Jennifer Karolina (2023)
This project arises from the need to understand in a better way the sizing of capacitors for the power factor correction in the laboratory of the Technical University of Cotopaxi La Maná Extension, in the Electromechanical Career. This requirement emerge due to the non-linear loads that are installed, since the energy efficiency of an electrical system depends to a large extent on the compensation of reactive power that is carried out. From the fact of not having a network analyzer, the need to implement a portable multi-meter was decided, a Sentron PAC3120 equipment was used, equipment where the power quality of the three-phase installations existing in the laboratory can be visualized. Through the implemented cabinet, data was obtained for proceeding to size the capacitors. Initially, the basic concepts of the main electrical parameters such as active power, reactive power, apparent power, and power factor are presented, which serve to understand better the advantages obtained when performing the power factor correction. The norms imposed by CONELEC are also determined in case of working with a low or high power factor, determining that 0.96 is within the established range to avoid an economic sanction. It can be concluded that this implementation contributes to the academic and economic development of the university.